NATO's approach to the Libyan crisis in the events of the «Arab spring» - E. A. Repeshko (MGIMO University Press, 2014)
The modern system of international relations more often faces the conflicts of different tension which appear in different regions of the world. Conflicts of the beginning of XXI century are determined by different political, economic, national and confessional reasons. The system of international relations faced the crisis. This system had existed for many centuries and was adopted in the Westphalia Peace. The ending of the Cold War made the world see the new conditions whose distinctive feature was an increasing quantitative index of clashes. A number of political changes at the beginning of the current decade have resulted in changes of political regimes in these countries. On the whole, the process of peaceful political transformation was characteristic of the events of the so-called «Arabic spring». However, similar changes in Libya proved to have a different character causing military changes and NATO's military intervention. If the process of social uprising turned into protest-street disturbances in Egypt and Tunis, in Libya there was an armed overthrow of the authorities by the opposition supported by foreign states. The author touches upon the events of the Arabic spring which resulted in overthrowing Gaddafi's regime. NATO' policy was criticized in the course of military actions in Libya. The author considers NATO's views, particularly, that of the USA, France and Great Britain in terms of the Libyan crisis and its solutions. The study of the conflict mechanism, its nature will allow to estimate taken by the world measures influencing the modern system of international relations.